Pengaruh Moralitas Individu Dan Efektivitas Pengendalian Internal Terhadap Kecurangan Akuntansi Di LPD Kecamatan Kerambitan - Ni Putu Dina Ayu Cipta Dewi; Kadek Dewi Padnyawati; Ni Made Wisni Arie Pramuki (UNHI Press, 2023)
This study aims to examine the effect of individual morality and the effectiveness of internal control on accounting fraud at the Village Credit Institution in Kerambitan District. The population in this study were 90 respondents consisting of the LPD chairman, secretary, treasurer, and LPD supervisory body from 26 LPDs located in Kerambitan District. The analytical technique used in this research is SEM-PLS. The results of this study are individual morality has a positive and significant influence on accounting fraud, the higher the individual's morale, the higher the chance of accounting fraud, allegedly because the respondents involved in this study are still in the pre-processing stage. conventional theory, where according to Kohlberg's moral theory, someone who has individual morality at the preconventional stage, then the opportunity for accounting fraud to occur will be higher. the occurrence of accounting fraud is getting bigger. Allegedly this happened due to the low regulation in an organization (LPD) and the low sanctions given to perpetrators of fraud, so that it did not provide a deterrent effect to the perpetrators.